“You is got a monst’us heap ter l’arn yit”: Charles Chesnutt’s Revisions of Albion Tourgée’s ‘Carpetbagger’ and ‘White Negro’ Characters - Koy, Christopher E. (American & British Studies Annual, 2010)
Arguably the greatest advocate for Civil Rights among whites in the Reconstruction and post-Reconstruction periods, Albion Winegar Tourgée (1838-1905) influenced the African-American novelist Charles Chesnutt (1858-1932) significantly. Both authors were born in Ohio, wrote fiction and nonfictional essays about the desperate situation of Blacks in the South during and after Reconstruction, and both ended their respective careers with a sense that their reception was either ignored or misunderstood.